Variabilidade genética, estrutura populacional e identidade molecular dos marsupiais Didelphis albiventris e Marmosops incanus no Brasil - Luciene Cassia Correa de Sousa (2013)
We studied population genetics aspects of two species of the family Didelphidae and the suitability of the DNA barcode methodology to effectively identify them. A molecular study of a 653 bp sequence of cytochrome c oxidase, subunit I from 40 Didelphis albiventris froman urban fragment of the Brazilian Atlantic Forest, showed three closely connected haplotypes, low nucleotide diversity and a haplotype diversity of 59.1%. We confirmed the sympatry between D. albiventris and D. aurita for the BHMR region, located on the capital of Minas Gerais state, and also for the 94 Km distant Piracema region, using DNA barcode methodology, which demonstrates the suitability of these techniques to effectively discriminate between these opossum species. Expanding the population surveys of D. albiventris, we used the COI fragment to 93 biological samples from seven Brazilian localities with linear distances ranging between 58 and about 1800 km, to study the effect of geographicdistances on variability and genetic differentiation. The haplotype network exhibits nine haplotypes distributed in two genetic clusters completely compatible with the two distant geographic areas of Minas Gerais, Southeastern Brazil, and Rio Grande do Sul, South Brazil. Within each cluster we observed low nucleotide diversity and high haplotype diversity,suggesting that their populations are composed of closely related haplotypes. Moderate to high FST differentiation values were observed and a very weak phylogeographic signal characterized interdemes comparisons within Minas Gerais, which were correlated with thepresence of closely and exclusive haplotypes. In a larger geographic scale, comparisons between Minas Gerais and Rio Grande do Sul produced a high FST values and a strong phylogeographic pattern. As Didelphis dispersion rates are recognized to be greater in males,they probably contribute more for gene flow. Working with a maternal inherited genetic marker, we can not argument about complete D. albiventris diversity. Our results informed only on the mutational history that corresponds to maternal lineages genealogical information.The observed scenario was unexpected and strongly suggests that mtDNA gene flow was not enough to maintain population cohesion. As expected, Marmosops incanus showed completely different results. M. incanus shows significant habitat preference and has been pointed out as an indicator species, being sensitive to habitat fragmentation (Rocha et al., 2011). It also exhibits ecological characteristics like low mobility and semelparity (Lorini et al. 1994; Loretto & Vieira, 2008), which can compromise interdemes connection. We studied a 509 bp fragment of COI obtained from specimens collected in 17 Brazilian localities andobserved the influence of geographic distance in genetic differentiation among populations. The genetic distances between demes haplotypes and the great number of forms produced a network with a large number of steps between some studied haplotypes. Large FST, indicating strong genetic structure, great values for phylogroups variation and elevated correlation between genetic and geographical distances characterized interpopulational analyses. Haplotype network and phylogeographic trees clearly showed molecular haplogroups mostly compatible with geographic clustering. The observed pattern of geographic distribution ofgenealogic lineages showed strong phylogeographic signal; our findings, specially the great divergence values between demes, suggest that, more than one effect of habitats fragmentation, M. incanus life history is central to explain the observed results. The strong genetic structure and the great variation among phylogroups are related to ancient processes that influenced lineages geographic distribution reflecting fragmentation events that predate human driven habitat destruction. M. incanus ecological characteristics, like low mobility and high sensibility to habitat fragmentation, are not suitable to gene flow, allowing the maintenance of high levels of genetic differentiation.